L’europeismo ai tempi dell’Illuminismo: Jean-Jacques Rousseau - Erminio Maglione (Rosenberg & Sellier, 2015)
This analysis of passages from Rousseau’s political work intends showing the structuring of the reflection about the Europeanism in his philosophy. The chosen parts describe how Europe should be at the time of enlightened rationalism with an explicit programmatic intent: it should be organized by the principle of federalism based on an international arbitration able to guarantee the costums and the common Christian-Roman origin.